2021
DOI: 10.1093/jbcr/irab240
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Danger of Lithium Battery-Powered Electric Bicycles and Scooters: A Case Series of the Israeli National Burn Center Experience

Abstract: Electric powered bicycles and scooters that use rechargeable lithium batteries are an urban transportation alternative and have become increasingly popular. However, in recent years, there has been an increase in patient admissions to the Israeli National Burn Center with burns associated with their use. In this case series of all patients (n=9) referred to the Emergency Department (February 2016 - October 2020) with lithium related battery burns from electric powered bicycles and scooters, we present burn dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…4,5,[25][26][27][28][29] At the same time, studies have identified other, less common risks such as burn injuries from exploding batteries and potential environmental harm due to inappropriate battery disposal in water sources. [30][31][32] Given the already increasing popularity of EMMs, the fact that interest and injury rates increased even more during 2020 and 2021 is alarming. The COVID-19 pandemic intensifies the need for public awareness about the dangers of EMMs and for safety measures to mitigate these dangers.…”
Section: Rise Of Electric Bicycles and Electric Micromobility Vehicle...mentioning
confidence: 99%
“…4,5,[25][26][27][28][29] At the same time, studies have identified other, less common risks such as burn injuries from exploding batteries and potential environmental harm due to inappropriate battery disposal in water sources. [30][31][32] Given the already increasing popularity of EMMs, the fact that interest and injury rates increased even more during 2020 and 2021 is alarming. The COVID-19 pandemic intensifies the need for public awareness about the dangers of EMMs and for safety measures to mitigate these dangers.…”
Section: Rise Of Electric Bicycles and Electric Micromobility Vehicle...mentioning
confidence: 99%
“…1 In all countries, new sources of energy to switch from classical fossil fuels have emerged as the focus of attention. 2 With the benefits of high energy density, high output capacity, and high performance-to-price ratio, lithiumion batteries have been broadly applied and promoted in the area of renewable energy. 3 Application of which allowed the construction of utility electric vehicles as well as satisfying a number of stringent milestones for electric vehicle economy in regards to energy density, lifetime, security, performance and expense.…”
mentioning
confidence: 99%